Antibiotic-Impregnated Bone Grafts in Orthopaedic and Trauma Surgery: A Systematic Review of the Literature. (25th June 2012) - Anagnostakos, Konstantinos; Schröder, Katrin
Abstract : There exist several options for local antibiotic therapy in orthopaedic and trauma surgery. Over the past years, the use of antibiotic-impregnated bone grafts (AIBGs) has become a popular procedure in the treatment of bone and joint infections. A major advantage of AIBGs involves the possibility of impregnation of various antibiotics depending on the sensitivity profile of the causative organism, whereas an additional surgery with removal of the antibiotic carrier is not necessary, as in the use of antibiotic-loaded bone cement. However, generalized conclusions cannot be clearly drawn from the existing literature due to differences of bone used, impregnation method, antibiotics, their doses, laboratory circumstances, or clinical indications. The present work reviews the literature regarding this topic and sheds some light onto the choice of bone and antibiotics, manufacturing details, and clinical experience.